Kritik Arsitektur terhadap Pergeseran Nilai Vernakular pada Revitalisasi Alun-Alun Tasikmalaya - Keane Dylan Alexander; Utami .; Rendiyansyah Maulana Herwin (GLOBAL SCIENTS PUBLISHER, 2026)
The town square (alun-alun) is a crucial element in traditional Javanese urban planning. It holds philosophical, spiritual, social, and political significance. As the city center, the alun-alun reflects the harmonious relationship between humans, nature, and God. Furthermore, it serves as a symbolic space that accommodates interactions between the people and the authorities. Tasikmalaya's town square, located in the city center of the East Priangan region, has undergone significant changes since the colonial era. This transformation continues with the implementation of a modern revitalization program from 2022 to 2024. This study aims to examine the shift in local values ​​and architectural identity resulting from changes in the town square's physical form, spatial function, and symbolic meaning. The method used in this study is a descriptive qualitative approach based on architectural criticism. This was conducted through historical studies, field observations, analysis of aerial photography documentation, and interviews with residents. The results show that the revitalization of Tasikmalaya's town square has successfully improved the visual quality, cleanliness, and comfort of the public space. However, on the other hand, these interventions diminish these values, including the spontaneity of social interaction, the sacredness of space, and the spiritual connection between the town square and the mosque, which are key elements of Javanese urban planning. Therefore, a revitalization approach based on local wisdom, or re-vernacularization, is needed. This approach aims to restore the town square's social, religious, and symbolic functions as part of the city's cultural identity.